Iraq in the Contents of The Myths of The Bididian and The Ancient Persian Kiynism Families) A Critical and Analytical Reading - Al-Taie, Osama Kadhim Omran (International Journal of Psychosocial Rehabilitation, 2020)
The study is carried out an intellectually homogeneous historical vision "within the framework of the legendary dimension lurking in the stomachs of the preserved Islamic sources, a share of the legendary Persian quotations that reflected in their designs the symbolic emotions manifested in the precursors of the ancient Persian literary texts that reflected the ranges of its unbridled desire to place Iraq between the palm of their pincers and the announcement of its return to them, through the presentation of news with a focused tone in the framework of the political dependence of the Persians, declaring this by waving to fictitious governments of legendary Persian kings pretending of two ancient Persian families, the Biddas family and the entity. The results of the study manifested itself in the field of critiquing and deconstructing these texts in an "semantic" position, And come up with new structural employments of the text by subjecting it to semantic approaches and matches with sources with new Iraqi sources, which predicted the invalidity of the old Persian mythological claims and their lack of realism was clearly evident ''In the legend of Purasib, which indicated his ownership on the land of Mesopotamia, merging his era with the era of the Prophet Noah, peace be upon him, without knowing the old one and his lack of synchronization with him, since he was contemporary'' of the stone age in the history of ancient Iraq, in which no monarchy or any other regime was witnessed.